Sexual practices and risky sexual behaviours among public secondary school adolescents in a local government area in Ekiti State, Nigeria - Ojo JO; Ipinnimo TM; Alao TA; Alabi OS; Adeojo OM; Ilevbare MO; Olorunfemi BN; Esan FJ; Adejumo JO; Dailo CO; Ubulom KA; Ogbonna KO; et al. (Ibom Medical Journal)
Background: Sexual practices and risky sexual behaviours among adolescents have great consequences on their health, well-being, and career prospects. We assessed sexual practices and risky sexual behaviours among public secondary school adolescents in Ido/Osi Local Government Area, Ekiti State, Nigeria.